A study of teaching and learning about the paradoxical concept of physical and chemical change - Palmer, William Pitt (Curtin University, 2003)
Science is sometimes seen as contained in a little box on its own, separate from the rest of the world. The questions underpinning this thesis set in train thoughts about investigating the chosen topic, the teaching and learning of physical and chemical change, using a very wide range of methodologies. The perspective is of someone involved in the teaching of the physical sciences for more than 40 years. The topic still remains contentious in teaching chemistry.The thesis sets out the evidence for and against the teaching of physical and chemical change and tracks the historical origins of the concept, its changing definitions and the research relating to the concept of physical and chemical change. A number of historically based textbook case studies are presented, some of which the author considers to be pioneering. The study ends with consideration of the public understanding of science, wondering whether the concept of physical and chemical change can be helpful in this respect.The conclusions reached are not in themselves remarkable, expressing a belief, that overall the concept of physical and chemical change is of benefit to the chemical community and perhaps to the wider public.